Hilangnya Rasa Percaya Diri Anak Dalam Proses Pembelajaran Seringkali Disebabkan Oleh Kurangnya Komunikasi Efektif Antara Guru Dan Siswa - Anggraini, Elya Siska; Purba, Gloria Verintina Sari; Lingga, Imel Betsaida; Buulolo, Sefrin Hewi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Self-confidence is one of the important aspects in supporting children’s success in the learning process. However, in practice, many students still experience decreased self-confidence, especially when asked to express opinions or answer questions in class. This study aims to examine the relationship between effective communication between teachers and students and children’s self-confidence levels in teaching and learning activities. The method used is a descriptive qualitative approach through observation and interviews with teachers and elementary school students. The results of the study indicate that the lack of open two-way communication, minimal appreciation, and communication patterns that tend to suppress or reprimand directly cause children to feel emotionally insecure. This has an impact on children’s courage to be active in learning. These findings emphasize that effective and empathetic communication from teachers is essential to creating a learning environment that supports the development of children’s self-confidence